Layers upon layers: data sharing & reuse challenges in archaeological contexts - Olsson, Michael; Sköld, Olle; Andersson, Lisa (Information Research an international electronic journal, 2024)
Introduction. This short paper presents preliminary findings from a study of archaeologist’s information practices relating to data sharing and reuse. Method. Semi-structured remote interviews were carried out with 16 archaeologists relating to their research interests, their data creation, use and reuse practices, as well as the general views on the importance of data sharing and reuse in archaeology. Analysis. Analysis was undertaken using an inductive, thematic approach informed by Kemmis et. al.’s (2014) practice architectures model. Results. The findings demonstrate that participants’ data sharing and reuse information practices feature cultural-discursive, material-economic, and social-political arrangements and that these three forms of arrangements are often interrelated. Conclusion. The practice architectures framework can make a significant contribution to both finding solutions to some of the key issues that have hampered the development of the Open Data movement, as well as offering possibilities for new avenues of information practices research.